Replacing the triethanolamine in Wolbers’ resin and bile soaps - Camille Polkownik (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In the 80’s, Richard Wolbers introduced the resin and bile soap to the conservation world. Despite the numerous advantages these products offer, studies mentioned the residues most likely caused by the triéthanolamine. This article explains how soaps work, resumes quickly the conclusions of the studies and reports the attempts of the replacement of triethanolamine in the soaps. First, a brief introduction about soaps will explain their uses, applications and cover the different recipes. Then, a short literature review will be done, introducing the practical part of the study, which is about replacing one of the problematic ingredients of the soaps.